2016
DOI: 10.3389/fpsyt.2015.00179
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of the Habenular Circadian Clock in Addiction

Abstract: Drug addiction is a brain disease involving alterations in anatomy and functional neural communication. Drug intake and toxicity show daily rhythms in both humans and rodents. Evidence concerning the role of clock genes in drug intake has been previously reported. However, the implication of a timekeeping brain locus is much less known. The epithalamic lateral habenula (LHb) is now emerging as a key nucleus in drug intake and addiction. This brain structure modulates the activity of dopaminergic neurons from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 107 publications
(128 reference statements)
1
11
0
1
Order By: Relevance
“…It has been previously shown that the geniculohypothalamic tract (which includes the IGL), actively modulates SCN responses to retinal input (Hanna et al 2017) and might modulate metabolic signals to the SCN (Saderi et al 2013), and reward and metabolic signals of feeding to the LHb (Huang et al 2019). Also, it is widely known that the LH and the LHb are deeply involved in the control of metabolism, food intake and motivational processes Salaberry and Mendoza 2016), which could explain our findings in this study.…”
Section: Groupssupporting
confidence: 64%
“…It has been previously shown that the geniculohypothalamic tract (which includes the IGL), actively modulates SCN responses to retinal input (Hanna et al 2017) and might modulate metabolic signals to the SCN (Saderi et al 2013), and reward and metabolic signals of feeding to the LHb (Huang et al 2019). Also, it is widely known that the LH and the LHb are deeply involved in the control of metabolism, food intake and motivational processes Salaberry and Mendoza 2016), which could explain our findings in this study.…”
Section: Groupssupporting
confidence: 64%
“…The habenula constitutes-together with the stria medullaris and pineal gland-the epithalamus and consists of medial and lateral parts [8]. The habenula has received much attention because of it asymmetry in certain vertebrate species [9] and its role in mediating biorhythms [10]. The habenula regulates the intensity of reward-seeking and misery-fleeing behaviour probably in all our vertebrate ancestors.…”
Section: Introductionmentioning
confidence: 99%
“…It receives projections from retinal ganglion cells and is involved in reward processing for relevant control of monoaminergic system in the VTA (for DA) and raphe nuclei (for 5-HT) (Hattar et al 2006;Baker and Mizumori 2017). Moreover, the LHb possess oscillating properties which coordinate with the SCN to control circadian rest/activity rhythms (Mendoza 2017;Salaberry and Mendoza 2015), and short brief light pulses at the early night in Arvicanthis niloticus, but not in mice, increase c-Fos expression in the LHb (Shuboni et al 2015). As intermediary structures it is necessary to elucidate the respective contribution of the direct or indirect pathway of the modulation of mood by light.…”
Section: Discussionmentioning
confidence: 99%